Setting of the Coastal Area as A Mangrove Conservation Zone in Binanga Village Sendana District Majene District - Salma Laitupa; Andi Dewi Pratiwi (Faculty of Law, Musamus University, 2023)
Mangrove forests are an ecosystem element that is beneficial to the community, especially in the coastal area of ​​Binanga village, Sendana subdistrict, Majene regency. However, gradually the degradation of mangrove forests occurs which turns into community economic activities which indirectly erode the benefits of mangroves. The management and use of land in the mangrove forest area in Binanga village, Sendana subdistrict, Majene district, West Sulawesi province seems not to be optimal in managing spatial planning so that the mangrove vegetation is threatened with destruction. This research aims to provide an analysis regarding the regulation of coastal areas as mangrove conservation zones in Binanga village, Sendana District, Majene Regency. The type of research carried out is normative juridical with a statutory approach and a conceptual approach. The research results conclude that the policy of regulating coastal areas as mangrove conservation zones needs to be managed wisely and sustainably so that the impact of human activities can be controlled and some coastal areas are maintained for conservation. Apart from that, it is necessary to institutionalize mangrove resource management in Binanga village, by optimizing the role of the village government and establishing a Mangrove Forest Resource Management Institution (LPS-HM) in the village as a formal institution established by the Village Government.